The Dorsal Rather than Ventral Pathway Better Reflects Individual Syntactic Abilities in Second Language - Yamamoto, Kayako; Sakai, Kuniyoshi L. (Frontiers in Human Neuroscience, 2016)
The left inferior frontal gyrus (IFG) has been reported to be critically involved in syntactic processing, not only in first language (L1), but in second language (L2). Indeed, the leftward lateralization of the IFG has been shown to be correlated with the performance of a syntactic task in L2. Given that posterior language-related regions are systematically connected with the left IFG, the next question is which of the dorsal and ventral pathways is more critical to the individual syntactic abilities in L2. Here we used diffusion MRI and tractography with newly developed semi-automatic methods of defining seeds and selecting regions of interest (ROIs). We calculated mean thickness and fractional anisotropy (FA) in each ROI for the arcuate fasciculus (Arcuate) of the dorsal pathway, as well as for the inferior fronto-occipital fasciculus (IFOF) of the ventral pathway. In Experiment I, we performed partial correlation analyses between FA and the accuracy of the syntactic task, removing the effects of the accuracy of a spelling task, gender, and handedness. Among the two pathways in each hemisphere, only FA of the left Arcuate was significantly correlated with individual accuracy of the syntactic task. In Experiment II, we recruited monozygotic twins and examined to what extent their L2 abilities and their structural properties were similar. Within twin pairs, the highest significant correlation was observed for reaction times of the spelling task, while the correlation for the accuracy of the syntactic task was marginal; these two correlation coefficients were significantly different. Moreover, the thickness of the left Arcuate was highly correlated within pairs, while its FA, as well as the thickness/FA in the ventral pathways, was not significantly correlated. The correlation coefficient for the thickness of the left Arcuate was significantly larger than that of the left IFOF. These results suggest that the thickness of the left Arcuate is more associated with the shared genetic/environmental factors, whereas both of mutually correlated FA in the left Arcuate and individual syntactic abilities in L2 may be less prone to these shared factors.